Determinants of Cash Holdings in Developed and Developing Countries - Rafinda, Ascariena (JDM (Jurnal Dinamika Manajemen), 2018)
This paper aims to find out the determinants of amount of cash holdings in developed and developing countries. One of the reason is because majority of studies that exist only focus on developed countries such as US or UK. Therefore, it is important to study cash holdings in the context of developing countries as well. Samples are drawn from DataStream Database using a sample period between 2009-2014 by including recent output with firm selection criterion based on data availability of firms (Al-Najjar, 2013), whereas financial firms with SIC codes 6000-6799 were not included as well as utility firms with SIC codes 4000-4999, resulting in total sample of 5402 observations from 23 countries. EViews was employed for the regression analysis with amount of cash holdings as the dependent variable. The results show that most of the hypotheses are not confirmed because of insignificant results and/or unexpected signs of coefficients. As the research about cash holdings in developing countries is not extensive yet, it is possible that there are differences to be found between developed and developing countries.